DIFERENSIASI PRODUK DAGING BUAH PALA PADA GRAND MERCIFUL BUILDING - Bonita L.M. Rawis; Celcius Talumingan; Esry H. Laoh (Universitas Sam Ratulangi, 2016)
ABSTRACTThis study aims to determine the differentiation to be carried out on meat products nutmeg on Grand Merciful Building and to determine their value-added meat products nutmeg done time after differentiation. This study uses data obtained by direct interview with the manager C.V Novita in Grand Merciful Building. The data used in this study are primary data. Variable-yuang variables measured in penelelitan include four criteria of differentiation according to Kotler form, features, durability, reliability and design. The study lasted from December to January from preparation, data collection, to preparing the results of the research report. The research location is in the city of Manado. The results of this study indicate that the meat product differentiation nutmeg there are six kinds: 1) candied nutmeg divided into three (3) kinds of sweet, spicy, dry, 2) dodol nutmeg, 3) Aseman nutmeg / Ci'um, 4) Candy nutmeg , 5) Butter nutmeg, 6) nutmegsyrup, divided 2 (two) types of palm sugar and white sugar. From the results of 6 product differentiation there is no added value in each product with the highest total added value contained in nutmeg syrup white sugar Rp. 31.43 million in the period of October 2015 and the lowest total added value contained in nutmeg butter products amounted to Rp.76,900.